2023
DOI: 10.7554/elife.85679
|View full text |Cite
|
Sign up to set email alerts
|

An umbrella review of systematic reviews on the impact of the COVID-19 pandemic on cancer prevention and management, and patient needs

Abstract: The COVID-19 pandemic led to relocation and reconstruction of health care resources and systems, and to a decrease in healthcare utilization, and this may have affected the treatment, diagnosis, prognosis, and psychosocial well-being of patients with cancer. We aimed to summarize and quantify the evidence on the impact of the COVID-19 pandemic on the full spectrum of cancer care. An umbrella review was undertaken to summarize and quantify the findings from systematic reviews on impact of the COVID-19 pandemic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
0
13
0
1
Order By: Relevance
“…For example, a recent US study reported that the frequency with which six established primary care screening quality measures were done declined by 2/3 in the early months of the pandemic and was still 1/3 lower when COVID-19 cases had declined markedly between the first and second waves 16 . Unfortunately, there are also now multiple analyses demonstrating declines in new cancer diagnoses and worsening prognosis for those detected (presumably later in their disease course) [17][18][19][20] as well as poorer maternal and fetal outcomes 21 during the COVID pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent US study reported that the frequency with which six established primary care screening quality measures were done declined by 2/3 in the early months of the pandemic and was still 1/3 lower when COVID-19 cases had declined markedly between the first and second waves 16 . Unfortunately, there are also now multiple analyses demonstrating declines in new cancer diagnoses and worsening prognosis for those detected (presumably later in their disease course) [17][18][19][20] as well as poorer maternal and fetal outcomes 21 during the COVID pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed a substantial impact of the COVID-19 pandemic on cancer care (Linjawi et al 2023 ). Depending on the geography and study design, varying degrees of delays and cancellations of cancer treatment, screening and diagnosis have been observed, leaving the medium- and long-term impact on cancer care uncertain (Muka et al 2023 ). By analyzing a total of 30,171 patients with gastrointestinal malignancies from five different European countries from IQVIA’s Oncology Dynamics (OD) database (Alymova et al 2022 ), we show that for 1342 (4.5%) patients, a treatment delay occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has also led to delays in diagnostic tests, imaging studies, and surgeries, resulting in longer wait times for the patients (Teglia et al 2022 ; Mazidimoradi et al 2021 ; Teng et al 2022 ; Dorri et al 2021 ). Moreover, the pandemic has discouraged many people from visiting cancer treatment facilities for fear of contracting the virus (Muka et al 2023 ). A recent umbrella review summarized and quantified the results of available systematic reviews on the impact of the COVID-19 pandemic on cancer treatment modification, delays, and cancellations (Muka et al 2023 ), showing a decrease in screening rates across all cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Focused efforts should estimate excess deaths from various non‐COVID‐19 causes during 2020–2023 and beyond, for example, from disruption of healthcare services regarding acute cardiovascular disease, 52 chronic diseases such as cancer, 53 reversal in progress on infectious diseases such as malaria 54 or tuberculosis, 55 hunger/starvation, 56 mental health deterioration, 57 drug overdose epidemics 49 and diverse worsening circumstances 58 . The quality of relevant data varies across countries and extrapolations require great caution.…”
Section: Causal (Mis)interpretation Of Excess Deathsmentioning
confidence: 99%